Conceptualising (dis)advantage in South African higher education: A capability approach perspective - Gore, Oliver Tafadzwa; Walker, Melanie (Critical Studies in Teaching and Learning, 2023)
Higher education policy in South Africa uses the concept of ‘historically disadvantaged’ to address inequities and inequalities. Disadvantage specifically refers to black students who are marginalised in higher education due to structural factors associated with the apartheid legacy of segregation. In this paper, drawing from the capability approach, the authors argue that (dis)advantage can be better understood in terms of students’ capabilities, functionings, and agency, which go beyond race to address other forms of oppression like class, gender and related individual factors. Students with a wider capability set and agency to convert resources into capabilities and functionings are deemed advantaged in comparison with those who have a narrower capability set and lack agency. Based on theory and empirical findings, this paper offers a complex, multidimensional and nuanced conceptualisation of (dis)advantage to understand practical interventions in higher education. The findings show that foregrounding race in addressing disadvantage is limiting and policy should therefore provide opportunities to all students for them to succeed.